Systematic Assessment of Growth Factor Treatment on Biochemical and Biomechanical Properties of Engineered Articular Cartilage Constructs - Elder, Benjamin D. (2008)
OBJECTIVE: To determine the effects of bone morphogenetic protein-2 (BMP-2), insulin-like growth factor (IGF-I), and transforming growth factor-β1 (TGF-β1) on the biochemical and biomechanical properties of engineered articular cartilage constructs under serum free conditions. METHODS: A scaffoldless approach for tissue engineering, the self-assembly process, was employed. The study consisted of two phases. In the first phase, the effects of BMP-2, IGF-I, and TGF-β1, at two concentrations and two dosage frequencies each were assessed on construct biochemical and biomechanical properties. In phase II, the effects of growth factor combination treatments were determined. Compressive and tensile mechanical properties, glycosaminoglycan (GAG) and collagen content, histology for GAG and collagen, and immunohistochemistry (IHC) for collagen types I and II were assessed. RESULTS: In phase I, BMP-2 and IGF-I treatment resulted in significant, >1-fold increases in aggregate modulus, accompanied by increases in GAG production. Additionally, TGF-β1 treatment resulted in significant, ~1-fold increases in both aggregate modulus and tensile modulus, with corresponding increases in GAG and collagen content. In phase II, combined treatment with BMP-2 and IGF-I increased aggregate modulus and GAG content further than either growth factor alone, while TGF-β1 treatment alone remained the only treatment to also enhance tensile properties and collagen content. DISCUSSION: This study determined systematically the effects of multiple growth factor treatments under serum-free conditions, and is the first to demonstrate significant increases in both compressive and tensile biomechanical properties as a result of growth factor treatment. These findings are exciting as coupling growth factor application with the self-assembly process resulted in tissue engineered constructs with functional properties approaching native cartilage values.